Adsorption properties and synthesis of silica aerogel-hollow silica microsphere hybrid (sandwich) structure - Guler, Omer; Selen, Veyis; Basgoz, Oykum; Safa, Hasan; Yahia, Ibrahim S. (Springer, 2021)
Silica aerogels have the potential use in many applications due to their large specific surface area and high porosity. One of these applications can be adsorption. However, their major disadvantage is their very low strength. Si-aerogels can be dispersed in adsorption processes with strong mechanical mixing and their removal from the solution environment becomes difficult but also their reuse becomes impossible. Therefore, mechanical strength of the adsorbent was increased with the sandwich structure synthesised in this study and it was aimed to prevent deformations during its use. In this study, a sandwich type structure with silica aerogels in the outer part and hollow silica microspheres in the inner part was synthesised. The sandwich structure was produced and characterised with a hybrid process in which production of aerogel from rice hull and hydrolysis-condensation method were used together with hollow silica microsphere production methods. The produced sandwich structure was used as an adsorbent in removing the dye material from aqueous solutions containing methylene blue (MB) dye. In the process of removing MB dye from aqueous solutions with silica aerogel-hollow silica microsphere sandwich (SAE-HS) structure, the maximum adsorption capacity was calculated as 35.94 mg/g. While it was concluded that the adsorption of MB dye with SAE-HS structure is highly dependent on pH, it was determined that there was an increase in the adsorption efficiency with the increase of pH. As a result, the sandwich structure showed a successful adsorbent property. Its high efficiency recovery was achieved. The sandwich structure has the potential to be developed as an adsorbent with a higher adsorption capacity. [GRAPHICS] .
Keywords: Silica aerogel; Hollow silica microsphere; Sandwich structure; Methylene blue; Adsorption; Response surface methodology (RSM)